2016
DOI: 10.5606/archrheumatol.2016.5915
|View full text |Cite
|
Sign up to set email alerts
|

Application of Diffusion-Weighted Imaging in the Detection of Active Sacroiliitis and the Comparison of Apparent Diffusion Coefficient and Relative Apparent Diffusion Coefficient Values

Abstract: Objectives: This study aims to evaluate the role of diffusion-weighted imaging in detection of active sacroiliitis and compare the apparent diffusion coefficient (ADC) and normalized relative ADC (r-ADC) values by using vertebra and iliac wings as reference organs. Patients and methods:The study included 56 patients (26 males, 30 females; mean age 37.7±10.1 years; range 18 to 66 years) with chronic back pain and without history of sacroiliitis who underwent magnetic resonance imaging. T2-weighted spectral pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Diffusion weighted imaging (DWI) based on the random and thermal (Brownian) motion of water which can be quantified by calculating apparent diffusion coefficient (ADC) values in square millimeter per second depending on the degree of water molecule diffusion at in vivo MRI [8][9][10][11][12]. ADC values obtained from DWI can be affected by menstrual cycle and hormone replacement therapy [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diffusion weighted imaging (DWI) based on the random and thermal (Brownian) motion of water which can be quantified by calculating apparent diffusion coefficient (ADC) values in square millimeter per second depending on the degree of water molecule diffusion at in vivo MRI [8][9][10][11][12]. ADC values obtained from DWI can be affected by menstrual cycle and hormone replacement therapy [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Hence the degree of tissue water diffusion is inversely associated with the cellularity of the tissue and the cell membrane integrity. Based on this phenomenon, DW-MRI can be used to evaluate many pathologic conditions in the body and can help differentiate cellularity of the histologic structure [8][9][10][11][12].…”
Section: Early Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…Of course, we cannot omit the fact that several previous authors reported the high relevance of quantitative assessment of ADC value in the differentiation of axSpA and non-inflammatory lesions [7,[18][19][20][21][22][23] as well as in the monitoring of axSpA treatment [8,24]. The mean ADC was higher in patients with an active axSpA in comparison to patients with low back pain of mechanical origin [20,21], Modic 1 changes in spine [22,23] and healthy individuals [18][19][20]. Furthermore, according to previous research, ADC value measured within the bone lesions correlates with C-related protein level [7], disease activity (BASDAI-Bath Ankylosing Spondylitis Disease Activity Index), functional impairment (BASFI-Bath Ankylosing Spondylitis Functional Index) and patient global assessment (BASGI-Bath Ankylosing Spondylitis Global Index) scores [25].…”
Section: Discussionmentioning
confidence: 99%
“…First of all, a reliable methodology of ADC value measurement should be developed and uniformed between the future studies. Currently, some authors perform a direct measurement of ADC value [7,18,20,21], while the others calculate the relative ADC value [10,19], referring it to an unaffected bone, for instance, in the midline of the sacral bone [10]. Additionally, in some reports, there is a comparison between ADC value within the inflammatory lesions and to the one measured within the unaffected bone [7,10,18,20,21], while in the others, mean ADC value from regions unaffected by bone marrow oedema or structural changes is globally assessed and compared between the sides and the groups with and without axSpA [19].…”
Section: Discussionmentioning
confidence: 99%